2020
DOI: 10.21203/rs.3.rs-55958/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors of Secondary Infections in Severe and Critical Patients Hospitalized with COVID-19: A Case-Control Study

Abstract: Background: Severe patients hospitalized with COVID-19 suffered secondary infections which greatly increased the length of hospital stay and the mortality. We aimed to explore risk factors of secondary infections that can help clinicians early implement preventive measures to dispose of severe and critical inpatients with COVID-19.Methods: A case-control study enrolled 238 severe and critical patients with COVID-19. Characteristics of cases and controls were compared.Results: Severity of illness on admission, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…[44] Additionally, those with low levels of protein were more likely to go on to develop a second infection, thus implying that low protein levels might indicate a compromised immune system. [45] Albumin is a common protein measured in the body and decreased levels are seen in liver disease. Our study has identi ed key historical and objective measurements that were demonstrated to be predictive of increased inpatient mortality in those hospitalized with COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…[44] Additionally, those with low levels of protein were more likely to go on to develop a second infection, thus implying that low protein levels might indicate a compromised immune system. [45] Albumin is a common protein measured in the body and decreased levels are seen in liver disease. Our study has identi ed key historical and objective measurements that were demonstrated to be predictive of increased inpatient mortality in those hospitalized with COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Two articles [12,17] investigating PPI use and risk of secondary infection were found in the database, we combined them and found that PPI use was associated with increased risk of secondary infection. (OR=4.33, 95% CI=2.57-7.29, P<0.001; I 2 =0%, P heterogeneity =0.570) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of seven studies [9][10][11][12][13][14][15] on risk of COVID-19 infection found that the use of PPI was not associated with increased or decreased risk of COVID-19 infection (OR:1.64, 95%CI = 0.54-5.00, P=0.390; I 2 =100%, P heterogeneity <0.001). (Figure 2 The result of nine studies from eight original articles [7,9,[16][17][18][19][20][21] showed that PPI use was associated with increased risk of severe disease, including admission to ICU,…”
Section: Association Between Ppi Use and Risk Of Covid-19 Infectionmentioning
confidence: 99%
“…Two articles (12,17) investigating PPI use and risk of secondary infection were found in the database, we combined them and found that PPI use was associated with an increased risk of secondary infection. (OR=4.33, 95% CI=2.57-7.29, P<0.001; I 2 =0%, Pheterogeneity =0.570) (Figure 5).…”
Section: Association Between Ppi Use and Risk Of Secondary Infection For Covid-19 Patientsmentioning
confidence: 99%